Functional activation independently contributes to naming ability and relates to lesion site in post‐stroke aphasia. Issue 4 (13th January 2017) - Skipper‐Kallal, Laura M.; Lacey, Elizabeth H.; Xing, Shihui; Turkeltaub, Peter E.
Abstract: Language network reorganization in aphasia may depend on the degree of damage in critical language areas, making it difficult to determine how reorganization impacts performance. Prior studies on remapping of function in aphasia have not accounted for the location of the lesion relative to critical language areas. They rectified this problem by using a multimodal approach, combining multivariate lesion‐symptom mapping and fMRI in chronic aphasia to understand the independent contributions to naming performance of the lesion and the activity in both hemispheres. Activity was examined during two stages of naming: covert retrieval, and overt articulation. Regions of interest were drawn based on over‐ and under‐activation, and in areas where activity had a bivariate relationship with naming. Regressions then tested whether activation of these regions predicted naming ability, while controlling for lesion size and damage in critical left hemisphere naming areas, as determined by lesion‐symptom mapping. Engagement of the right superior temporal sulcus (STS) and disengagement of the left dorsal pars opercularis (dPOp) during overt naming was associated with better than predicted naming performance. Lesions in the left STS prevented right STS engagement and resulted in persistent left dPOp activation. In summary, changes in activity during overt articulation independently relate to naming outcomes, controlling for stroke severity. Successful remapping relates to network disruptions that depend on the location of the lesion in the left hemisphere. Hum Brain Mapp 38:2051–2066, 2017 . ©2017 Wiley Periodicals, Inc.